Mining under kalina and Selisoo Bogs (ENVIRONMENT. TECHNOLOGY. RESOURCES. Proceedings of the International Scientific and Practical Conference, 2015)
Continuous developing of Estonian power engineering on the basis of oil shale requires ever taking into use of new exploration fields. When the reserve of Estonia mine is depleted, mining of the exploration field of Seli has to be started. But that field is located under the Selisoo bog which is defined as a region of the Natura 2000 network and is planned become a nature preserve. Conservationists are interested for what extent oil shale mining under the Selisoo bog and in its immediate nearness will spoil the natural water regime of the bog. To clear up the environmental impact are carried through several investigations in the Selisoo bog. As a result of modeling is proposed a perceptible lowering of water table in peat layer. At the same time we have a positive experience on mining under bogs and water bodies, some kilometers to the north from the Selisoo bog. In Viru mine situated under the Kalina bog there is oil shale mining practically finished for today, but the Kalina bog exists as before, also the Lake Kalina in this bog. The aim of this research is to compare the geological and hydrogeological parameters of the Selisoo and Kalina bogs, clearing up the essential factors owing to which the mining in district of the Selisoo bog could exert a larger influence on environment than under the Kalina bog. In this paper are some measures for diminishing of the environmental impact brought on.